Effects of school menstrual hygiene management, water, sanitation, and hygiene interventions on girls’ empowerment, health, and educational outcomes: Lasta district, Amhara regional state, Ethiopia - Fisseha A. Andargie; Femi R. Tinuola (PLoS ONE, 2025)
This study assessed the effects of school-based menstrual hygiene management (MHM) and water, sanitation, and hygiene (WASH) interventions on the empowerment, health, and educational outcomes of menstruating girls using cross-sectional and experimental designs. It examined whether access to MHM education and WASH facilities could enhance girls’ self-confidence, physical, emotional, and social health, class attendance, and academic performance. The results showed significant improvements in empowerment at intervention schools, with 54% of girls feeling confident purchasing sanitary products, compared to 18% in control schools, indicating better emotional well-being. Additionally, 21% and 22% of girls in intervention schools felt comfortable discussing MHM with boys and mothers, respectively, compared to just 9% in control schools, reflecting improved social health. Regarding physical health, 51% of menstruating girls in intervention schools practiced genital hygiene three to four times a day, compared to 33% in control schools. Educational outcomes were also improved, with 68% of girls in intervention schools attending class during menstruation, compared to 30% in control schools, and 78% reporting adequate study time at home, compared to 41% in control schools. However, no significant difference in academic performance was found between the two groups. Overall, the findings suggest that school-based MHM and WASH interventions can significantly empower menstruating girls, improve their physical, emotional, and social health, and reduce menstrual-related absenteeism.